Effectiveness of Various Glycerol Concentrations as a Cryoprotectant in Frozen Semen of Pasundan Cattle - Siti Darodjah Rasad; N Solihati; K Winangun (Indonesian Center for Animal Research and Development (ICARD), 2022)
This study was conducted to determine the effectiveness of Glycerol as a cryoprotectant with various concentrations on the quality of Pasundan cattle semen. Semen was collected from seven bulls of Pasundan Cow using an artificial vagina twice a week for three months. The semen sample was added with a TRIS-Egg Yolk Extender containing 20% (v/v) egg yolk and treated with the addition of Glycerol with five different concentrations (G5=5%, G6=6%, G7=7%, G8= 8%, and G9=9%) were then performed with cryopreservation. A Completely Randomized Design (CRD) was used to examine the effect of five different concentrations of Glycerol on motility, intact plasma membrane (IPM), the integrity of acrosome cap (IAC), abnormalities, and recovery rate (RR) of spermatozoa after cryopreservation (post-thawing). The results of diluted Pasundan cattle semen evaluation showed that the addition of 7% Glycerol (G7) resulted in the best motility and IAC values (83.68% and 72.84%), the addition of 7% and 8% Glycerol (G7 and G8) resulted in the best IPM values (85.00% and 84.50%). The addition of 6%, 7%, 8%, and 9% Glycerol (G6, G7, G8, and G9) resulted in the lowest abnormality values (1%). On the post-thawing Pasundan cattle semen evaluation, the addition of 7% Glycerol (G7) resulted in the best motility, IAC, IPM, and RR values (54.49%, 38.57%, 54.29%, and 72.28%). Meanwhile, adding various Glycerol concentrations did not significantly affect the abnormality value of post-thawing spermatozoa. Generally, the addition of 7% Glycerol in semen extenders shows optimal results as a cryoprotectant.